2023
DOI: 10.3390/cells12151942
|View full text |Cite
|
Sign up to set email alerts
|

Microglia–Astrocyte Interaction in Neural Development and Neural Pathogenesis

Abstract: The interaction between microglia and astrocytes exhibits a relatively balanced state in order to maintain homeostasis in the healthy central nervous system (CNS). Disease stimuli alter microglia–astrocyte interaction patterns and elicit cell-type-specific responses, resulting in their contribution to various pathological processes. Here, we review the similarities and differences in the activation modes between microglia and astrocytes in various scenarios, encompassing different stages of neural development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 106 publications
0
10
0
Order By: Relevance
“…It has been reported that glial cells such as oligodendrocytes, astrocytes, and microglia play a significant role in the development, growth, maturation, and activity of neurons [ 59 ]. Microglial cells account for approximately 5–20 % of the glial cells in the central nervous system (CNS).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that glial cells such as oligodendrocytes, astrocytes, and microglia play a significant role in the development, growth, maturation, and activity of neurons [ 59 ]. Microglial cells account for approximately 5–20 % of the glial cells in the central nervous system (CNS).…”
Section: Discussionmentioning
confidence: 99%
“…They contribute to forming a glial reparatory tissue near the injured tissue, aiding in debris clearing and wound compaction. Microglia play a significant role in astrocyte proliferation and induce astrocytic conglomerate formation through cytokine secretion [49]. However, the impact of microglia on astrocytes is not limited to only the induction of astrocyte proliferation; based on microglial phenotype, astrocytes can be activated and change their characteristics, as is detailed further on.…”
Section: Microglia In the Context Of Spinal Cord Injurymentioning
confidence: 97%
“…Additionally, astrocytes interact with other glial cells such as microglia, potentially escalating neuroinflammatory responses and influencing disease progression. Their capability for phagocytosis, which is essential for cleaning up myelin debris and dead cells, can also become maladaptive, leading to sustained inflammation and the inhibition of regenerative processes (Sun et al, 2023).…”
Section: Astrocytesmentioning
confidence: 99%
“…Inflammation in ALS involves both reactive microglia and astrocytes. Mutant superoxide dismutase 1 released from motor neurons triggers microglial and astrocytic activation, contributing to the inflammatory process (You et al, 2023). Dendritic cells, T cells, microglia, and macrophages produce cytokines and chemokines that promote inflammation.…”
Section: Multiple Sclerosis Huntington's Disease and Amyotrophic Late...mentioning
confidence: 99%